SIZE DISTRIBUTION OF JAW CRUSHER CRUSHING PRODUCTS FOR ROUNDED MATERIAL - Sumarjono, Erry; Misdiyanta, Partama; Fahrudinoor (Institut Teknologi Nasional Yogyakarta, 2024)
Abstract — Crushing is one of stage material size reduction in mineral processing. Jaw Crusher is one of the equipment that used to reduction size material and it’s generally used in primary crushing. Feed of crushing is come from mined material (Run of Mine-ROM) that have various shapes like very rounded, rounded, angular etc. Rounded material is one of them. The aim of this research is to calculate the size distribution and the pattern of size distribution product of crushing for rounded material. The equipment of crushing in this research was used Jaw Crusher in Mineral Processing Laboratory, Institut Teknologi Nasional Yogyakarta which 30 samples material. The same pattern of size distribution was obtained from the +4#, -4#+10#, -10#+20#, -20#+40#, -40#+60#, -60#+100#, -100#+200# dan -200# product size distribution. The biggest amount of size distribution was obtained in 4#. Limiting Reduction Ratio (LRR) were distributed in range 4-6. Losses percentage (% losses) of material crushing were less than 10%. Keywords: Crushing, limiting reduction ratio, losses, mineral processing, primary